Development of a Symptom Management Intervention: Qualitative Feedback From Advanced Lung Cancer Patients and Their Family Caregivers. Issue 1 (January 2017) - Mosher, Catherine E.; Ott, Mary A.; Hanna, Nasser; Jalal, Shadia I.; Champion, Victoria L.
Abstract : Background: Little is known about cancer patient and family caregiver preferences for the content and format of nonpharmacologic interventions. Revising interventions based on patient and caregiver feedback before implementation may improve intervention feasibility and acceptability, especially in the context of advanced-stage cancer. Objectives: The aim of the study was to obtain feedback from patients with advanced-stage, symptomatic lung cancer and their family caregivers on the content and format of a nonpharmacologic symptom management intervention under development. The intervention blended evidence-based cognitive-behavioral and emotion-focused strategies to reduce physical and psychological symptoms. Methods: Semistructured qualitative interviews were conducted with 21 patients with advanced-stage, symptomatic lung cancer and caregivers. Participants reviewed handouts regarding intervention components and provided feedback. Results: Patients and caregivers desired intervention components that addressed the patient's high symptom burden such as education regarding treatment adverse effects and the provision of various coping tools. Offering interventions with a brief or flexible length and delivering them via telephone were other suggestions for enhancing intervention acceptability. Participants also preferred an equal focus on patient and caregiver concerns and a more positive intervention framework. Conclusions: Intervention preferences of patients with advanced-stage lung cancer and caregivers underscore the severity of the disease and treatment process and the need to adapt interventions to patients with high symptom burden. These preferences may be incorporated into future intervention trials to improve participant recruitment and retention. Implications for Practice: Nurses can modify interventions to meet the needs of patients with advanced-stage, symptomatic lung cancer and caregivers. For example, flexibility regarding intervention content and length may accommodate those with significant symptoms.